Optimizing the Role of PKK in Developing Family Food Security through Urban Farming in Sukojati Village, Banyuwangi - Nur Hafifah; Ahmad Syamsul Muarif (CENDEKIA: Jurnal Pengabdian Masyarakat, 2026)
This community service article describes the optimization of the Family Welfare Empowerment organization in strengthening family food security through urban farming in Sukojati Village, Banyuwangi. The activity used participatory empowerment involving needs assessment, socialization, technical training, household mentoring, monitoring, and evaluation. The partner was the Sukojati Village Family Welfare Empowerment team, with 40 members and families. Data were collected through observation, interviews, questionnaires, and production records. Results showed that productive yard use increased from 10 m2 to 25 m2 per family, catfish survival reached 85%, and 90% of participants were satisfied with the mentoring. The program also generated additional income of approximately IDR 200,000-400,000 per month.